Death on the Job: The Great Recession and Work-Related Traffic Fatalities - Michael French; Gulcin Gumus (Institute of Labor Economics (IZA), 2021)
In light of recent discussions about shifting employees from traditional workplaces to virtual employment, we are motivated by the question of whether this phenomenon will end up saving lives even in the absence of an infectious disease outbreak. Motor vehicle incidents are the leading cause of work-related fatalities in the US, killing more than 1,200 workers each year, which make up about a quarter of all work-related deaths. Not only are motor vehicle crashes the top killer at work, but economic expansions can further increase occupational and traffic deaths as they both tend to be procyclical. In this paper, we examine the effects of business cycles on traffic fatalities in the US with a special focus on work-related deaths. Specifically, we implement a longitudinal design across all 50 states by compiling quarterly data for 2004-2012 and consider macroeconomic fluctuations around the Great Recession. Our findings show that traffic deaths during prosperous times are not solely due to an increase in risky behaviors such as drunk driving, but directly related to work. Given the highly preventable nature of traffic crashes, policy makers, public health advocates, and employers can develop effective strategies, including remote work arrangements, to improve both occupational and traffic safety.
Keywords: E32; I12; I18; 330; traffic fatalities; occupational health; business cycles; unemployment; Great Recession